Parental Self-Efficacy dan Regulasi Emosi Anak Prasekolah: Dukungan Sosial Orang Tua Dapatkah Memperkuat? - Rana Dwinadia; Lia M Boediman (Fakultas Psikologi Universitas Tarumanagara, 2021)
Parental self-efficacy is one of the critical factors that impact emotional regulation development in preschool children. Many factors can impact parental self-efficacy; however, social support is often mentioned as one of the essential factors. Thus, this study aimed to explore the impact of parental self-efficacy and parental social support on preschooler's emotional regulation. Parental social support is used as a moderator variable, which can hypothetically strengthen the impact of parental self-efficacy on preschoolers' emotional regulation development. This research design was quantitative research. The participants consisted of 119 mothers of children in preschool age between the ages of five-to-six years old. The data were analyzed using the regression analysis method. This research found an impact of parental self-efficacy on preschoolers' emotional regulation and no impact on parental self-efficacy and parental social support on preschoolers' emotional regulation. Parental self-efficacy has an impact on preschooler's emotion regulation, but there is no effect of parental social support on parental self-efficacy.